Combined Effects of Barge Transportation, River Environment, and Rearing Location on Straying and Migration of Adult Snake River Fall‐Run Chinook Salmon. Issue 1 (2nd December 2016) - Bond, Morgan H.; Westley, Peter A. H.; Dittman, Andrew H.; Holecek, Dean; Marsh, Tiffani; Quinn, Thomas P.
Abstract: Homing and straying in salmon have been extensively studied, yet it has proven difficult to disentangle the biotic and abiotic factors that influence straying. In the Columbia River basin, some juvenile salmon are collected at dams and transported downstream to increase survival during seaward migration, and as returning adults they experience a range of environmental conditions as they ascend the river. We examined 8 years of PIT tag detection data for hatchery‐reared, fall‐run Chinook Salmon Oncorhynchus tshawytscha released in the Snake River to evaluate the combined effects of juvenile barging, rearing and release locations, and environmental conditions on adult migration speed and straying below and above the Columbia River–Snake River confluence. Straying to the upper Columbia River was 10–19 times more likely among adults that were barged as juveniles from Snake River dams than among adults that were in‐river migrants or that were transported from McNary Dam (below the confluence) as juveniles. Similarly, barging from Snake River dams and warmer Columbia River temperatures increased the likelihood of straying into streams below the confluence. Furthermore, adult upstream migration was slower among juveniles that were reared at two mid‐Columbia River hatcheries and juveniles that were barged, indicating possible navigational impairment. However, rearing location, release distance, and release age had relatively minimal effects on straying. Collectively, our results indicate that (1) adult migration and homing are affected by a complex combination of processes that take place during smolt out‐migration and the adult return migration, and (2) enhancement efforts can inadvertently add to the challenge. The straying of barged fish demonstrates the potential for increasing adult returns to the Snake River by changing the barging process so that it more adequately supports the proper imprinting of juveniles. Received May 13, 2016; accepted September 7, 2016 Published online December 2, 2016